Digital Storytelling Berbasis Budaya Sasak untuk Meningkatkan Literasi Peserta Didik SDN Sulin - Safinaturrahmah; Wardatul Uyun; Siharani; Fardiansyah; Malida Rahmawati; Dwi Novitasari (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
This community service activity aims to enhance teachers' skills in creating and utilizing digital storytelling with a Sasak cultural context to foster literacy interest among lower-grade students at SDN Sulin. The program was carried out in three phases: (1) Preparation, including coordination with partner schools, obtaining permissions, material development, socialization, and scheduling; (2) Implementation, covering storytelling introduction, design training, technology usage, trials, classroom implementation, Focus Group Discussions (FGD), and evaluation; (3) Final report preparation. Post-training survey results indicated an improvement in teachers’ understanding of digital storytelling and increased parental involvement in home literacy activities. Teachers successfully practiced and created digital storytelling and implemented it in classrooms, receiving positive responses from students. QR codes embedded in the storybooks enabled students to independently access learning materials, thereby expanding their learning opportunities. The outcomes also highlighted that culturally-based storytelling enhances students' literacy skills. Reading literacy tests on Sasak legend stories showed an improvement in students’ reading literacy after the introduction of digital storytelling books, with most students demonstrating good reading abilities and a solid understanding of the content